Pengolahan Sampah Buah dan Sayur dari Pasar Induk Mandalika Kota Mataram Nusa Tenggara Barat Sebagai Media Tumbuh Fusarium sp Inokulan Gaharu - I Gde Adi Suryawan Wangiyana; Arbi Sanjaya; Lutfi Anggadhania (IJEEM - Indonesian Journal of Environmental Education and Management, 2020)
The purpose of this research is to process fruit waste and vegetable waste from Mandalika Market at Mataram City as growth medium for Fusarium Sp agarwood inoculant. Collected fruit waste and vegetable waste were processed by grinding and filtrating into filtrate part and residue part. Filtrate part and residue part were formulated as combination growth media including: Fruit waste filtrate, vegetable waste filtrate, mix fruit-vegetable waste filtrate, fruit waste residue, vegetable waste residue and mix fruit-vegetable residue. Fusarium Sp. were sub-cultured into PDA before cultured on combination growth media. Colony diameter of Fusarium isolates were measured every day for seven days incubation period. Fusarium Sp. growth on media from fruit waste was better than its growth on media from vegetable waste. Fusarium Sp. has higher colony diameter on residue growth media compare to its colony diameter on filtrate growth media. On the other hand, filtrate growth media could support Fusarium Sp. to produce several pigmentations. This pigmentation could be an important key character for further taxonomical study. It could be concluded that fruit waste and vegetable waste from residue part could support maximum diameter colony of Fusarium Sp. while filtrate part of this waste could support Fusarium Sp. to produce pigmentation for taxonomical purpose.